(untitled) (Global Media Journal - German Edition, 2022)
It appears to be essential to reflect different perspectives for doing media development work in contexts where foreign actors are not insiders. Here, their outside views on the needs of supported countries and on how to work together can be difficult for implementing projects, especially for actors on-site on which this article focuses. It aims to bring practical and academic reflections together for a broader understanding of how insiders and outsiders perceive media development work differently. These different perceptions bring challenges to their relationship and cooperation. Based on the author’s research, a literature review, and interviews with practitioners from south-Asian media organizations, critical aspects will be discussed, such as cooperation dynamics, the effect of power inequalities, and subsequent trust difficulties. The article will not only give the perspective of actors on-site and their struggles with media development “cooperation,” but also suggest constructive approaches to work on an eye-level with mutual understanding.